Beyond SOx reductions from shipping: assessing the impact of NOx and carbonaceous-particle controls on human health and climate. (14th December 2020) - Bilsback, Kelsey R; Kerry, Deanna; Croft, Betty; Ford, Bonne; Jathar, Shantanu H; Carter, Ellison; Martin, Randall V; Pierce, Jeffrey R
Abstract: Historically, cargo ships have been powered by low-grade fossil fuels, which emit particles and particle-precursor vapors that impact human health and climate. We used a global chemical-transport model with online aerosol microphysics (GEOS-Chem-TOMAS) to estimate the aerosol health and climate impacts of four emission-control policies: (1) 85% reduction in sulfur oxide (SOx ) emissions (Sulf); (2) 85% reduction in SOx and black carbon (BC) emissions (Sulf-BC); (3) 85% reduction in SOx, BC, and organic aerosol (OA) emissions (Sulf-BC-OA); and (4) 85% reduction in SOx, BC, OA, and nitrogen oxide (NOx ) emissions (Sulf-BC-OA-NOx ). The SOx reductions reflect the 0.5% fuel-sulfur cap implemented by the International Maritime Organization (IMO) on 1 January 2020. The other reductions represent realistic estimates of future emission-control policies. We estimate that these policies could reduce fine particulate matter (PM2.5 )-attributable mortalities by 13 300 (Sulf) to 38 600 (Sulf-BC-OA-NOx ) mortalities per year. These changes represent 0.3% and 0.8%, respectively, of annual PM2.5 -attributable mortalities from anthropogenic sources. Comparing simulations, we estimate that adding the NOx cap has the greatest health benefit. In contrast to the health benefits, all scenarios lead to a simulated climate warming tendency. The combined aerosol direct radiative effect and cloud-albedo indirect effects (AIE) are between 27 mW m −2 (Sulf) and 41 mW m −2 (Sulf-BC-OA-NOx ). These changes are about 2.1% (Sulf) to 3.2% (Sulf-BC-OA-NOx ) of the total anthropogenic aerosol radiative forcing. The emission control policies examined here yield larger relative changes in the aerosol radiative forcing (2.1%–3.2%) than in health effects (0.3%–0.8%), because most shipping emissions are distant from populated regions. Valuation of the impacts suggests that these emissions reductions could produce much larger marginal health benefits (129–374 billion annually) than the marginal climate costs (12–17 billion annually).